Diagnosing reading problems for low-level Chinese as second language learners. (April 2021) - Yang, Shuyi
Abstract: Reading in a second language (L2) consists of lower-level linguistic processing and higher-level meaning integration. The lower-level processing has posed great challenges for beginning readers whose L1 (alphabetic language) is drastically different from their L2 (morphosyllabary Chinese). Diagnostic assessment is designed to identify readers' weaknesses in lower-level processing and allows language teachers to detect learners' reading problems and to conduct targeted remediation. However, few appropriate diagnostic tools are available for L2 reading and research on these tools' diagnostic effectiveness is scarce. The present study investigated the applicability of word reading, word segmentation, and text reading as diagnostic instruments for alphabetic-language-speaking, low-level Chinese L2 learners (n = 70). Results showed that all three instruments effectively identified weak readers, diagnosed reading problems, and pinpointed individual's difficulties. These findings offered empirical support for the three instruments as effective diagnostic tools in Chinese low-level L2 reading instruction and suggested the importance of developing lower-level processing skills. Highlights: Word reading, word segmentation, and text reading effectively discriminate weak low-proficiency Chinese L2 readers. Low-level Chinese L2 learners tend to make graphic errors in reading words and texts. Weak readers make unrelated errors in reading words and texts and combine non-word characters as words in segmentation. Weak readers are unexceptionally weak in word reading.